2015
DOI: 10.1007/s12040-015-0639-9
|View full text |Cite
|
Sign up to set email alerts
|

Trends in rainfall and rainfall-related extremes in the east coast of peninsular Malaysia

Abstract: The coastlines have been identified as the most vulnerable regions with respect to hydrological hazards as a result of climate change and variability. The east of peninsular Malaysia is not an exception for this, considering the evidence of heavy rainfall resulting in floods as an annual phenomenon and also water scarcity due to long dry spells in the region. This study examines recent trends in rainfall and rainfallrelated extremes such as, maximum daily rainfall, number of rainy days, average rainfall intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(65 citation statements)
references
References 40 publications
4
52
0
Order By: Relevance
“…Suhaila et al () and Wang et al () also reported an increase in the NEM rainfall in the IWC zone and almost no change of the SWM rainfall in Peninsular Malaysia for the periods 1975–2004 and 1971–2006, respectively. In the case of extreme rainfall events, Mayowa et al () found a substantial increase in p95 in the NE zone for the period 1971–2010. Syafrina et al () also reported an increase in p95 at nine out of 25 stations in the WC, NE and CT zones during the NEM over the period 1975–2010.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Suhaila et al () and Wang et al () also reported an increase in the NEM rainfall in the IWC zone and almost no change of the SWM rainfall in Peninsular Malaysia for the periods 1975–2004 and 1971–2006, respectively. In the case of extreme rainfall events, Mayowa et al () found a substantial increase in p95 in the NE zone for the period 1971–2010. Syafrina et al () also reported an increase in p95 at nine out of 25 stations in the WC, NE and CT zones during the NEM over the period 1975–2010.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of climate, it is a trend over more than 50 years where the cyclic or seasonal effect is minimal and the climatic effect is more (Antonio et al, 2018). Several studies have been conducted in Peninsular Malaysia in recent years to assess trends in rainfall and rainfall extremes (Wong et al, 2009;Deni et al, 2010;Suhaila et al, 2010aSuhaila et al, , 2010bMayowa et al, 2015;Syafrina et al, 2015;Othman et al, 2016;Wong et al, 2016). Various periods of data were used in those studies to report trends in different rainfall indices in Peninsular Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, the west coast of Malaysia is reasonably sheltered from southwest monsoonal storms by Sumatra. Furthermore, annual rainfall in eastern Peninsular Malaysia is becoming increasingly variable and torrential (Varikoden et al 2011;Mayowa et al 2015). The environmental differences on either side of Peninsular Malaysia are likely responsible, or at least contributing factors that are responsible, for generating the observed disparity in endosymbiont richness between the two regions.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing risk of flood in recent years has posed a major challenge in the Malaysian development [14], [15]. A number of recent studies revealed increasing frequency and severity of rainfall extremes in peninsular Malaysia [16], [17]. It can be anticipated that changes in rainfall pattern have not only changed the return period of flood peak, but also the flood duration and volume.…”
Section: Introductionmentioning
confidence: 99%